If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 13 = 4x + -42 Reorder the terms: 13 + x = 4x + -42 Reorder the terms: 13 + x = -42 + 4x Solving 13 + x = -42 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 13 + x + -4x = -42 + 4x + -4x Combine like terms: x + -4x = -3x 13 + -3x = -42 + 4x + -4x Combine like terms: 4x + -4x = 0 13 + -3x = -42 + 0 13 + -3x = -42 Add '-13' to each side of the equation. 13 + -13 + -3x = -42 + -13 Combine like terms: 13 + -13 = 0 0 + -3x = -42 + -13 -3x = -42 + -13 Combine like terms: -42 + -13 = -55 -3x = -55 Divide each side by '-3'. x = 18.33333333 Simplifying x = 18.33333333
| y=(50)x+b | | c/2-3.2=26.8 | | -2z=-z+9 | | -5(x-2)+8x=5x-6 | | 36+7n=6(n+7) | | 13=7+21t-16t^2 | | 10-4j-7=-9-7j | | 2x+6=3+6x-7 | | -7625+185t=0 | | 2q=18.92+6.3q | | 13.9j-9.71-8.7=9.43+16.3j | | -4y=-3y-10 | | 7x+4(x-5)=3(x+2)-5 | | 8x-3y=14fory | | 2x+5+6x-1=90 | | 3+10q=6+9q | | 3/4z=-5+1/2 | | 19.03+11.2y=5.1y-17.59-9.13 | | 4(-6x+1)=20-8x | | 335=5x^3 | | 8x+5-2x=-(5x-x) | | 3/4z=-5.5 | | 14.7t-5.79=15t | | 9h-(2h-4h+1)=38-2h | | 15.7g+18.66+7.2g=19.5g-13.64 | | -3(5a+6)=-5a+22 | | 0.7x-0.1=0.6x+2 | | 15x=2(1+9x) | | 2/3x=44 | | (5/9x)-(1/3)=3 | | -6r+1=-7r+20 | | 30+3x=-(3x+6) |